Occult breast carcinoma (To, N1, Mo): A conservative proposal - Santini, Alejandro; Torres, Miguel (Cirugía del Uruguay, 1997)
The authors analyse 1 O clinical charts of patients carriers of occult carcinoma of the breast, defined as To, N1, Mo and develop the reasons that make it possible to propase a conservative treatment of the breas t. They analyse the results of their series and those of reference authors and propase a future diagnostic-therapeutical guide that preserves the breast and is detailed in an algorythm.